Contextual Learning Animation Video for Science Subject Content in Grade IV Elementary School - Pasaribu, Noni Linzilah Mona; Suartama, I Kadek; Sukmana, Adrianus I Wayan Ilia Yuda (Universitas Pendidikan Ganesha, 2025)
The low student learning outcomes indicate the need for innovative instructional media that can enhance students' motivation and understanding. This study aims to: (1) design and develop a contextual-based interactive animated video as a learning medium for the topic